Intervensi Keperawatan Coaching Support pada keluarga terhadap upaya pemenuhan nutrisi Balita Stunting di desa Klungkung Sukorambi Jember (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Background and Aim: The state of malnutrition or chronic malnutrition that occurs in toddlers aged between 0-60 months, characterized by short stature and delays in growth and development is called stunting. The reported stunting rate is generally global, not differentiated by age range, so the exact number for each of these age ranges cannot be known. However, the average cases discussed were cases in groups of children or toddlers that received less attention. This condition causes toddlers to be very vulnerable to stunting. Toddlers who have experienced stunting are of particular concern, especially in fulfilling their nutrition. The family Coaching Support nursing intervention program is very important to increase the nutritional adequacy of these toddlers Methods: The research design uses a correlational design through a cross sectional model. The population used by the researchers was 64 children with a sample of 52 children using a proportional stratified random sampling technique. Bivariate analysis using the Spearman Rank correlation test. Results: The results of the study obtained a p value of 0.0005 <α 0.05 with a correlation of 0.3244 which means that the study has a moderate relationship between the coaching support nursing intervention model and the fulfillment of nutritional needs in children. Conclusion: The role of nurses, especially in community and family nursing, can be as a counselor assistant and as an educator related to understanding the form of family coaching support to preventing stunting or malnutrition in children according to family expectations in achieving the appropriate stages of child and family development Keywords ; nursing intervention, Coaching support, family, toddlers